PENGARUH WARNA RUANGAN TERHADAP KECEMASAN PASIEN SAAT PELAYANAN DI KLINIK GIGI - Rhama Pradipta Nabil Saputra; Ida Rahmawati; Emilda Sari (JURNAL TERAPIS GIGI DAN MULUT, 2021)
One of the problems faced for coloring a health facility, such as the practice room and its instruments, is because the practice room and its instruments have specificity in human services. Those who are served are human beings who need care, service, and healing, both physically and mentally. Such human beings certainly have a special emotional temperament. Therefore, the use of color in this case aims to "help" these service efforts. This study aims to determine the effect of room color on patient anxiety during services at the dental clinic. This type of research is a literature review research. The data used in the literature review research is secondary data that can be obtained from various forms of journals. The secondary data sources use 3 databases, namely: Google Schola, Pubmed, and Science Direct. Journals are searched based on keywords (keywords) and boolean operators (AND, OR, and NOT). The inclusion and exclusion criteria for the literature used the PICOS strategy. The findings of the journal indicate that there is an effect of room color on patient anxiety during services at the dental clinic. The conclusion of the color of a room can affect the emotions of a patient so that the selection of the right color can reduce the anxiety of the patient. As for suggestions for health workers to pay attention to the selection of the right color composition so that psychologically it can calm the patients in the room